Investigation of Measures for Material Flow Control for a Backward Extrusion of Geared Components from Coil - Leicht, Miriam; Henneberg, Johannes; Merklein, Marion (Lecture Notes in Mechanical Engineering, 2024)
Increasing ecological and economic demands are setting new requirements for industrial manufacturing processes and components. The use of functional integration as a strategy of lightweight design offers the possibility to meet these requirements. However, a high functional integration implies an increasing component complexity, which challenges conventional forming processes to their limits regarding formability and efficiency. The novel process class of sheet-bulk metal forming (SBMF) offers the opportunity to combine the advantages of sheet metal and bulk forming by applying bulk forming operations to sheet metal semi-finished products. SBMF from coil offers further economic and ecological benefits through high output rates, short process times by eliminating costly handling tasks and a greater material efficiency. However, forming from coil also poses coil-specific challenges such as anisotropic material flow and reduced geometric part accuracy. Against this background, in this study, a backward extrusion process from coil for forming geared functional components is investigated on a high-speed press. The objective of this study is to analyze measures for a targeted material flow control in order to avoid unequal material flow and to improve part accuracy. Therefore, the mild deep drawing steel DC04 with an initial sheet thickness of 2.0 mm is analyzed in a combined numerical-experimental approach. Within these investigations, the influences of coil width, friction and feed width are analyzed and evaluated based on component and process parameters. Finally, measures for a purposive material flow are derived.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Cold forming; Extrusion; Sheet-bulk metal forming